Continentia in the Confessions 8, 26-27 - Bruning, Bernard (Augustinianum, 2020)
This paper aims to show, on the one hand, that the humility mentioned in book 7 of the Confessions would become the prelude for Augustine to the humility that constitutes the true conversion, and, on the other hand, that the context in which this humility presented itself is continentia. In a passage of linguistic beauty (conf. 8, 27), Augustine describes the struggle that occurred between allegorical persons: those who pulled him back with the chain of the past, and those who urged him forward towards the decision to embrace continentia. The enjoyment of love not only requires the truth that remains forever, but also the steadfastness of all the emotions that come together in the lasting unity of the will. According to the author, Augustine in his Confessions has Christianised the Roman uirtus of continentia.